Bismuth titanate modified and immobilized TiO2 photocatalysts for water purification: broad pollutant scope, ease of re-use and mechanistic studies. Issue 12 (9th November 2018) - Odling, Gylen; Pong, Zhi Yi; Gilfillan, Gavin; Pulham, Colin R.; Robertson, Neil
Abstract : Bi4 Ti3 O12 –TiO2 on glass beads photodegrades pollutants including consumer-product precursors, pesticides, drugs and explosives. Abstract : Deposition of titanium dioxide (TiO2 ) coatings onto glass beads from a P25 enriched sol of titanium butoxide is described. This method gives a robust and stable covering, to which small bismuth containing clusters of 1–5 nm have been introduced using a simple and scalable sequential ionic layer adsorption reaction (SILAR) method. This bismuth-modified TiO2 coating has been proven to show significant improvements over the pristine TiO2 samples for a variety of different pollutants including intermediates in consumer product manufacture, pesticides, drugs and explosives. Using scavenger tests, the mechanism of degradation for each of the pollutant molecules tested has been probed, and a thorough discussion of the differences presented. The applicability of the system has also been assessed, with ease of re-use of the photocatalyst-bead apparatus investigated through recycling tests.